Effects of Exchange Rate Arrangements on Trade Cooperation in BRICS Countries - Shaygani, Bita; Hastiani, Asghar Abolhasani; Ghaffari, Farhad; shahdani, Mahdi Sadeghi; Fadaee, Mahdi (Asian Economic and Financial Review, 2015)
This paper investigated the effects of imposed exchange rate arrangements on trade volume of BRICS countries. This study examined emerging economies, were consists of Brazil, Russia, India, China, and South Africa during the years 2001-2013 using the generalized gravity model and a two-step generalized method of moments, (GMM). The results indicated that applying different exchange rate arrangements has had significant influence on imports. Pegged (PG) and crawling pegged (CP) exchange rate arrangements had significant and positive effect on trade flow (export). Bilateral imports, improved with imposing managed floating (MF) arrangements. Free-floating (FL) arrangements have been meaningless, and a negative impact on the volume of bilateral trade (exports) between members. In BRICS countries, imposing pegged exchange rate arrangements improved bilateral trade toward export and inversely free-floating arrangements improved bilateral trade toward import.